A novel flow control valve for pulsating flows - Chaugule, V.; Narayanaswamy, Ramesh; Narayanan, V.; Jewkes, J.; Lucey, A. (2014)
The design and performance characteristics of a mass flow control valve to generate unsteady pulsating flows are presented in this paper. As the majority of the naturally occurring flows are pulsatile in nature, it becomes imperative to simulate these flows for their experimental analysis. The proposed flow control valve is capable of producing controlled, periodic pulsating mass flows having sinusoidal, triangular, and trapezoidal waveforms to be used for fluid dynamics research. The design of the valve, while being simple, allows for generation of pulsatile flows over wide range of amplitudes and frequencies. Distinct waveforms for the output flows, at two amplitudes and frequencies, are demonstrated experimentally, and compared with the conceptual design.